Association Between Dental Caries and Sociobehavioral Factors Among Female Students in Secondary Schools and College of Dentistry in Babylon Province - Aqeel Handil Al Jothery; Ahmed Ghanim Al Helal (Medical Journal of Babylon)
Background: Continuous changes in socioeconomic and lifestyle aspects in Iraq have incurred a lot of adverse effects on oral health quality, especially among adolescents. However, minimal studies have been conducted among adolescent females concerning the prevalence of dental caries (DC). Objectives: This cross-sectional study aimed to investigate the prevalence of DC and its severity concerning different aspects of sociobehavioral (SB) factors among female students in secondary schools and dental colleges in Babylon Province, Iraq. Materials and Methods: About 500 students from both Al-Tali’a secondary school (16–18 years) and Babylon Dental College (19–20 years) were recruited in this study from March to May 2023. DC was assessed based on the decayed, missing, and filled teeth index (DMFT) scores, and SB and socioeconomic factors were obtained from a structured questionnaire. Results: The prevalence of DC was high (98.6%), and its association with measured SB factors was not significant. However, the severity of DC was positively (P < 0.05) associated with sugar intake and previous dental visits, but negatively (P < 0.05) associated with the frequency of brushing and household wealth index. Conclusion: The results here highlight the considerable effects of SB factors on the severity of DC, which in turn reflect a poor education of oral health among adolescent females in Babylon City, and it also recommends the desperate need for creating preventive programs for reducing the occurrence of DC among the students.